Association between volatile organic compounds exposure and cardiometabolic function: a population-based study - Qiuyu Wang; Yongping Cao; Fei Ma; Hengyang Zhang; Yuelin Hu; Wenwen Xiao (Frontiers in Public Health)
BackgroundThe Cardiometabolic Index (CMI) is a new metric used to assess an individual’s cardiovascular and metabolic status. Volatile Organic Compounds (VOCs) are common environmental pollutants associated with cardiovascular diseases and lipid metabolism disorders. This study aims to investigate the relationship between VOC exposure and CMI.MethodsData from NHANES (2011–2020) were used to assess the impact of VOC exposure on cardiometabolic function. Multivariable linear regression was used to analyze the association between VOCs and the CMI. Restricted cubic spline models were applied to model the nonlinear relationship between VOCs and CMI. BKMR (bayesian kernel machine regression), WQS (weighted quantile sum), and Q-gcomp (quantile g-computation) models were employed to explore the association between VOC mixture exposure and CMI. Subgroup analyses were conducted to investigate the relationship between VOCs and CMI across different subgroups.ResultsMultiple linear regression analysis confirmed the significantly positive associations between the highest quartile concentrations of CEMA, 3HPMA, MHBMA3, and HMPMA compared to the lowest quartile (β = 0.43, 95% CI = 0.20, 0.67, P for trend < 0.001; β = 0.30, 95% CI = 0.05, 0.55, P for trend = 0.006; β = 0.37, 95% CI = 0.14, 0.61, P for trend < 0.001; β = 0.28, 95% CI = 0.01, 0.55, P for trend = 0.010). AAMC and SBMA showed a nonlinear relationship with CMI. Results from mixture exposure models indicated that CEMA contributed most significantly to the impact on CMI. BKMR, WQS, and Q-gcomp models showed a positive trend between overall VOC exposure and CMI. Subgroup analysis revealed significant interactions of BMI and diabetes status in the relationship between VOC exposure and CMI, especially among individuals with BMI ≥ 30 and those with diabetes.ConclusionThis study found significant positive associations between specific VOC exposures and CMI. Additionally, BMI and diabetes status play important roles in moderating the relationship between VOC exposure and CMI. These findings highlight the potential impact of environmental VOCs on cardiovascular and metabolic health which provides new evidence for public health interventions.